(untitled) (International Journal of Ayurveda and Pharma Research, 2022)
In the present era of modernization and fast life, everybody is over busy and living a very stressful life. Faulty dietetic habits and sedentary life style is responsible for early degenerative changes in bodily tissue. As per Ayurveda, Greevastambha has been described under Vataj Nanatmaja Vikaras. Few Lakshanas of Kupitoanilah such as Pani-Prishta-Shirograha, Gatrasuptata, Greevaya-Hundanama, Bhedastoda-arti are the well-known features of Greevastambha. Greevastambha can be correlated with Cervical Spondylosis of modern medical sciences. Cervical Spondylosis is a degenerative condition of cervical spine that affects the vertebral bodies and intervertebral disc of the neck as well as contents of the spinal canal. It leads to pain and stiffness in neck, radiating pain into arm, headache, vertigo, dizziness, paraesthesia, numbness etc. Material and Methods- Patients fulfilling the diagnostic and inclusion criteria were selected for the present study from the OPD/IPD of our institute. The present study was carried out in a single group of 10 patients. In the present study, Snehana Nasya along with Greevabasti with Karpasasthyadi Taila was taken to evaluate the combined effect in the management of Greevastambha w.s.r. to Cervical Spondylosis. Result- Statistically significant results were observed in the present study.